The experience of performing concurrent elective circumcision during paediatric laparoscopic inguinal hernia repair - Ab. Rahman, Norhafiza; Abdul Aziz, Dayang Anita; Lim, Felicia; Teo, Rufina; Osman, Marjmin (2019)
Aim: Circumcision is a common procedure with indications ranging from medical to non-medical reasons. Elective circumcision (EC) in this context refers to a circumcision done on a non-diseased penis as part of cultural or religious purposes, as recommended by the Islamic religion. The number of EC performed is high in the Muslim predominant countries like Malaysia. In Universiti Kebangsaan Malaysia Medical Centre (UKMMC), EC is frequently added as an additional procedure to laparoscopic inguinal hernia (LIH) repair. The purpose of this study is to obtain objective data on this practice. Methods: This is an observational, ambispective cohort study of about five years duration comparing two groups of patients, those who had both LIH repair and EC and those who only had LIH repair. Outcomes of interest were post-operative morbidity and rate of recovery. Results: 237 patients aged between one month and 12 years underwent LIH repair for patent processus vaginalis (PPV). Post-operative complications were higher in the combination surgery group (4%) compared to LIH repair group (3.3%). However, both peri-operative morbidity and recovery outcomes did not show overall significance in this study (p = 0.770). The addition of EC was not associated with increase in the rate of complication over the abdominal wound, prolonged duration of post-operative hospitalization, worsen post-operative pain score and delay in return to routine activity. Conclusion: Performance of EC during LIH repair is safe and did not cause any significant added morbidity and prolonged recovery